DEFENSIVE INJURIES IN HOMICIDE VICTIMS: A TEN-YEAR RETROSPECTIVE AUTOPSY STUDY - Subakov, Neda; Ciric, Marija; Milosevic, Veljko; Gojkovic, Tijana; Cibic, Aleksandra; Bogdanovic, Milenko; Petrovic, Tijana; Radnic, Bojana; Banjanin, Irina (Medical Research, 2026)
Background: Defensive injuries represent a key forensic indicator of a victim’s attempt to resist an assault and hold substantial value in distinguishing homicide from suicide. This study aimed to analyze the frequency, forensic and other characteristics of defensive injuries in homicide victims and to assess their relationship with demographic factors, injury mechanisms, and weapon types.Methods: A retrospective cross-sectional analysis was conducted on 161 homicide autopsies performed between 2014 and 2023 at the Institute of Forensic Medicine in Belgrade, Serbia. Data on demographics, weapon type, and injury patterns were statistically evaluated, including descriptive and analytical statistic methods, with significance set at p < 0.05.Results: Defensive injuries were identified in 56 cases (34.8%), most commonly bilateral and polymorphic, localized in the upper third or diffusely along the forearms. They occurred significantly more often in sharp- and blunt-force homicides (p < 0.001) and nearly absent in firearm-related deaths. Male and elderly victims exhibited higher rates of defensive injuries.Discussion: Defensive injuries are typically located on the upper limbs. The distribution of defensive injuries depends on multiple factors, including the weapon used, attack’s direction, the assailant’s approach, and the relative body positions of both individuals. Numerous, widely distributed defensive injuries, present in large numbers, may point to a prolonged and dynamic struggle. Conclusion: The recognition and interpretation of defensive injuries provide valuable insight into the dynamics of homicide, enabling accurate forensic reconstruction and contributing to the legal classification of homicide cases.
Keywords: homicide; defensive injuries; weapon; autopsy; interpersonal violence